2006
DOI: 10.1007/s11270-006-9181-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Kinetics and Effects of Operating Parameters on the Performance of a Methyl Tert-Butyl Ether Degrading Biofilter

Abstract: The goals of the study were to determine the effectiveness of a laboratory-scale biofilter on the removal of methyl tert-butyl ether (MTBE) and investigate the operating parameter effects on biofilter performance. The experimental results show that average MTBE removals of 53.6-93.2% were observed at loads of 2.5-20.1 gm −3 h −1 and an empty-bed residence time of three minutes, after continuous operation for four months throughout the biofilter acclimation period. After a one-day recovery period operation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…S-3b). Indeed, an increase in EBRT, giving rise to a longer contact time between the contaminated air and the biofilm on the packing material, is known to give a higher value for r m 16,27,28 . If these r m values are compared with previous studies, see Table 4, it appears that the macadamia nutshells as packing material perform similarly to the best carriers used in comparable studies.…”
Section: Biodegradation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-3b). Indeed, an increase in EBRT, giving rise to a longer contact time between the contaminated air and the biofilm on the packing material, is known to give a higher value for r m 16,27,28 . If these r m values are compared with previous studies, see Table 4, it appears that the macadamia nutshells as packing material perform similarly to the best carriers used in comparable studies.…”
Section: Biodegradation Kineticsmentioning
confidence: 99%
“…To illustrate the effect of temperature variation in the mesophilic range on the reactor performance, the biofilter was also operated at temperatures ranging from 292 to 313 K. To measure the biofilter activity over the reactor depth, the biofilter was designed with several axial sampling ports, so an axial concentration profile through the reactor could be recorded. An important trend in biofiltration is to determine the biokinetic parameters using existing models, as these parameters may differ considerably from those found in the literature depending on the experimental conditions under which the parameters were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalent use of methyl tert-butyl ether (MTBE) in reformulated fuel to further reduce emissions of carbon monoxide and other smog-related air pollutants has led to its introduction into groundwater from spills and leaky underground storage tanks (Baehr et al 1999;Klinger et al 2002;Chiu et al 2006;Dong et al 2007;Zhong et al 2007 ). In the USA, Landmeyer et al (2001) tested all of the wells adjacent to an MTBE storage tank and found MTBE to be present at the milligram per liter level, with even concentrations >10 mg/L MTBE being found.…”
Section: Introductionmentioning
confidence: 99%